Between "Chaos" and "Order": the Representation of the "Sounds" in the Work of Pedro Cieza de León, Primera parte de la Crónica del Perú - Eiris, Ariel Alberto (2021)
Fil: Eiris, Ariel Alberto. Pontificia Universidad Católica Argentina; Argentina